The impact of an educational program using semi-sports in learning some basic movements of preschool children (4-5 years) Field study in kindergarten-theniet methane chir-batna - redouane benhamza; kasdi hamida (sports creativity, 2025)
The aim of this study is to find out the effect of a proposed educational program using semi-sports in learning the basic motor skills of a preschool child (4-5 years). And knowledge of the importance of semi-sports in the share of physical education and sports and their impact on the process of learning for the child. To achieve the objectives of the study, the experimental method was used. The original community reached 131 children andchildren. The sample size was 44 children and girls randomly selected. An educational program consisting of educational units and motor tests was used as a tool for study. The statistical analysis was used for the stenting test. The study indicated that there was learning of the basic motor skills of both groups with a preference for the experimental group in all kinetic tests Keywords: educationl programs - Semi-sports games - Play when the child- Pre-school child (4-5) years - Basic motor skills